Influence of Light Exposure during Cold Storage of Minimally Processed Vegetables (Valeriana sp.) - Angela Zappia; Alessandra De Bruno; Rosita Torino; Amalia Piscopo; Marco Poiana (Journal of Food Quality)
Minimally processed vegetables are sensitive to leaves discoloration and quality deterioration, and these negative aspects can affect their shelf life. During the manufacturing processing, Valeriana leaves were submitted to different dipping acid solutions and then were stored at cold temperature in dark and in light to study the influence of the light exposure on their quality in terms of total free acidity, dry matter percentage, colour, water activity, total bacterial count, antioxidant components, and total antioxidant activity. The results suggest that dark storage is recommended for a better physicochemical quality of Valeriana leaves. In particular, light influenced significantly the browning index and hue angle with a significance level of p<0.01 and p<0.05, respectively, whereas both exposure conditions affected total bacterial count and pH (p<0.01). Dipping treatments had an effect on pH, aw, and total bacterial count, while the storage time influenced with highly significant differences the most of the studied parameters, except for the antioxidant compounds.